Judgment and decision making under stress: an overview for emergency managers - Kathleen M. Kowalski-Trakofler (The National Institute for Occupational Safety and Health (NIOSH), 2003)
This paper discusses human judgment and decision making under stress. The authors review selected recent literature across various disciplines and suggest a definition of stress within the context of decision making during the management of emergencies. They also discuss fieldwork by the Pittsburgh Research Laboratory, NIOSH, which explores traumatic incident stress, the relationship between previous training and performance under stressful conditions, and human behaviour in underground mine fires. The authors assert that stress is one of the factors that decision makers must contend with in most life-or-death situations. They suggest that a better understanding of individual judgment and decision making activities whilst under stress would yield a better understanding of how people reach the choices they make in emergencies. This enhanced understanding would be of enormous value to emergency managers, researchers and policymakers.